Association of Youth Characteristics and Recent Utilization of Dental Services in the United States - Chertok, Ilana R. A.; Chertok, Nathaniel; Haile, Zelalem T.; Chavan, Bhakti (Frontiers in Pediatrics, 2018)
Background: Oral health is important for overall health of youth, although dental service utilization is lower than national goals. The purpose of the study was to identify sociodemographic and health behavioral characteristics of youth in the United States who reported having at least one dental visit in the past 12 months. Methods: Secondary data analysis was conducted using the 2015 Youth Risk Behavior Survey (YRBS) to examine factors associated with dental care utilization using Andersen’s theory-based Behavioral Model of Health Care Utilization. Results: Among 5,814 youth, nearly 78 percent reported visiting a dentist in the past 12 months. After adjusting for potential confounders, characteristics significantly associated with higher likelihood of dental care utilization were: predisposing factors of non-Hispanic white ethnicity and health behavior characteristics of not using tobacco, not using illegal substances, not drinking soda, and wearing a seat belt; enabling factor of speaking English well; and perceived health of not being overweight. Discussion: Use of the Healthcare Utilization Model identified significant factors classified as predisposing, enabling, and need-related factors associated with youth’s utilization of dental care services. Findings from the theory-based population-based study informs healthcare providers of factors to consider when promoting dental care among youth.